Distinct metastatic organotropism shapes prognosis in lung adenocarcinoma with brain metastasis - Sayin, Sama I.; Eklund, Ella A.; Ali, Kevin X.; Dzanan, Jozefina J.; Xylander, Moe; Dankis, Martin; Lindahl, Per; Sayin, Volkan I.; Hallqvist, Andreas; Wiel, Clotilde (Frontiers in Oncology, 2025)
BackgroundMetastatic organotropism in lung cancer significantly influences prognosis, yet current treatment and clinical management guidelines are largely generalized for metastatic disease, regardless of organ site involvement. Notably, up to 30% of non-small cell lung cancer (NSCLC) patients present with brain metastases (BM) at diagnosis, underscoring the need for a more nuanced understanding of metastatic patterns. However, real-world clinical data on metastatic organotropism in well-characterized patient cohorts remain surprisingly scarce. Here, we evaluate patterns of metastasis, clinical characteristics and survival outcomes in patients with lung adenocarcinoma (LUAD), the major histological NSCLC subtype.MethodsWe performed a multi-center retrospective study including 913 stage IV LUAD patients, diagnosed and molecularly assessed in western Sweden between 2016–2021. Our primary study outcome was the distribution of specific metastatic sites and its impact on Overall Survival (OS).ResultsOut of 913 stage IV LUAD patients, 23.4% had BM. These patients exhibited markedly different metastatic patterns compared to those without BM, and median survival was significantly shorter (6 months) than those without BM (7.8 months) (p = 0.021). In addition, more than one metastatic tumor in the brain coincided with worse OS, compared to those with no, or with only one metastatic tumor in the brain. Importantly, OS was also influenced by metastasis in specific extracranial organs, like the pleura and lungs.ConclusionsOur study highlights the distinct metastatic patterns and survival outcomes associated with BM in stage IV LUAD. These findings emphasize the need for site-specific approaches in managing metastatic disease due to BM’s impact on survival.